Friends with boys - Hicks, Faith Erin, ....- (New York : Square Fish, 2015)
After years of homeschooling, Maggie is starting high school. It's pretty terrifying. Maggie's big brothers are there to watch her back, but ever since Mom left it just hasn't been the same. Besides her brothers, Maggie's never had any real friends before. Lucy and Alistair don't have lots of friends either. But they eat lunch with her at school and bring her along on their small-town adventures. Missing mothers...distant brothers...high school...new friends... It's a lot to deal with. But there's just one more thing. MAGGIE IS HAUNTED.
Keywords: Engels; Friendship; Graphic Novels; Secundair onderwijs